Quantitative detection of Staphylococcus aureus using aptamer-based bioassay coupled with porous Si SERS platform - Divagar Muthukumar; Giorgi Shtenberg (Journal of Science: Advanced Materials and Devices, 2024)
The current study presents a highly sensitive and selective surface-enhanced Raman scattering (SERS) based method for detecting Staphylococcus aureus (S. aureus) in food and water samples. The bioassay includes target bacteria recognition by a specific aptamer complex, fast syringe filtration and the assessment of unbound biorecognition complexes using a silver-coated porous silicon SERS platform. Notably, the developed bioassay showed high sensitivity toward S. aureus detection, achieving an impressive detection limit of 2 CFU mL−1 and a broad linear response of 101–106 CFU mL−1. Furthermore, the selectivity, regeneration and overall shelf-life were thoroughly evaluated while depicting satisfactory performances. Finally, the practicality of the developed SERS bioassay was elucidated in various samples (i.e., fish, milk, groundwater and tahini) spiked with different S. aureus concentrations that revealed recovery values of 93–110%. The successful validation of actual samples' analysis emphasizes the platform's reliability, robustness and suitability for practical use, including on-site operation.